Examining Significant Factors Influencing Workers' Safety Behavior in Project Work Environments - Rully Rahim; Novandra Rhezza Pratama (Journal of Social Research, 2026)
This study investigates the key factors influencing construction workers' safety behaviour, focusing on safety knowledge, safety awareness, safety intervention, and safety rules and procedures. A mixed-methods approach was employed, starting with a conceptual model developed through a literature review and validated via the Delphi method with safety experts. A quantitative survey was then conducted with construction workers, and data were analysed using partial least squares structural equation modeling (PLS-SEM) to test the hypothesised relationships. The findings show that safety knowledge and safety awareness have significant direct effects on safety behaviour. Safety rules and procedures impact safety behaviour both directly and indirectly by enhancing safety knowledge, while safety intervention plays a crucial role in shaping safe work practices. Additionally, importance–performance map analysis (IPMA) identified key areas that require immediate managerial focus for improving safety performance. This research contributes to the safety behaviour literature by providing an empirically validated model specific to the construction sector. Practically, it offers actionable insights for project managers and safety practitioners to develop targeted safety strategies that reduce occupational accidents in construction projects.